A Weighted Broadcast Routing Algorithm for WirelessHART Networks - Künzel, Gustavo; Cainelli, Gustavo Pedroso; Pereira, Carlos Eduardo (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2017)
This paper proposes an algorithm that uses predefined weights to create broadcast routes for a WirelessHART network. The network topology is represented by a graph, and the algorithm uses information of the devices present in the network to build the broadcast graph. At each iteration of the algorithm, a device is selected and then added to the broadcast solution graph. A cost function determines which device is selected. The cost function has weights related to four parameters of the devices: number of hops from the access point, type of energy source of the device, received signal level from neighbors and number of neighbors in the network topology. The cost function can be adapted to use other parameters in the construction of routes. This approach allows building routes that balance different application requirements. The algorithm was implemented in a static simulation environment and tested with different sets of weights. Some metrics were proposed to analyze the results, such as average number of hops of the broadcast graph, average received signal of the graph, among others. The results indicate that the use of weights change the resulting broadcast graph, which can improve the global network characteristics for certain applications.